Ivotuk Raw LAI Data. Version 1.0 ... - Epstein, H.; Riedel, S.; Walker, D. (UCAR/NCAR - Earth Observing Laboratory, 2007)
This is the Leaf Area Index (LAI) Raw Data taken from the Excel file of dataset "ATLAS: 1999, Ivotuk NDVI, LAI, and Phytomass Data (EXCEL) (Epstein)" and translated into Tabular ASCII. ...